Kajian Epidemiologi Deskriptif dan Faktor Risiko Kematian Coronavirus Disease 2019 (Covid-19) di Provinsi Riau - agus alamsyah; Ikhtiaruddin; Muhammadiah; Rajunitrigo Rajunitrigo; Nyimas Octa Elsa Aditia (Jurnal Kesehatan Komunitas, 2023)
COVID-19 is a global health problem including in Indonesia. Various interventions and policies have been implemented in controlling the Covid-19 pandemic, but the incident rate and Case Fatality Rate (CFR) from Covid-19 have continued to increase. Even the number of Covid -19 cases in Riau Province ranks 8th out of 34 provinces in Indonesia (RI Ministry of Health, 2021b). Research objectives Describe epidemiological characteristics and analyze risk factors for Covid-19 death in Riau Province. This research is an observational study using the NAR epidemiological investigation (PE) big database for the time period 5 April 2020- 5 April 2021. The study design is a descriptive cross-sectional study and an analytical cross-sectional study. all confirmed cases reported in the PE NAR recapitulation of Riau Province in the reporting period 5 April 2020-5 April 2021. The sample in this study was the total population (saturated sample). Univariate and bivariate analysis with chi-square test using software and computerization. The results of this study showed that there was a relationship between comorbidities (heart P value 0.001; COPD, pValue 0.0001; Kidney P Value 0.001 and Hypertension Pvalule 0.001) with Covid-19 mortality. So Covid patients who have comorbidities must be treated appropriately and quickly. For people who have comorbidities and must comply with health protocols.